The role of NGOs to improve food security in Bangladesh: the BRAC perspective - Hyder, SM Ziauddin; Husain, A.M. Muazzam (BRAC Research and Evaluation Division (RED), 2020)
Bangladesh is one of the worst food insecure nations in the world today. This paper looks into some food security issues of the poor, the most food insecure group, particularly with respect to the role of non-governmental organisations (NGO). Some learning from the development programmes of BRAC, which are directed to the poor women to improve their food security is briefly highlighted in this paper. A long-term commitment to the very poor as well as targeted efforts supported by short-term food subsidy is required to improve their situation on a sustainable basis. Effective partnership between the government, NGOs and donors is a key to the success in increasing the current food security situation.